Experimentation of Learning Cycle 7E Assisted by Labyrinth Board Game and Putar Bawah Game on Mathematical Reasoning Ability in View of Students' Self-Regulated Learning - Sutopo, Sutopo; Oktavia, Linda; Kuswardi, Yemi (International Journal on Emerging Mathematics Education, 2024)
This research aims to find out: 1) The learning model that produces better mathematical reasoning ability of students, between the Learning Cycle 7E assisted by labyrinth board game and putar bawah game or direct instruction; 2) The level of students' Self-Regulated Learning that produces bettermathematical reasoning skills, between high, moderate, or low levels of Self-Regulated Learning, ; 3) The interaction learning models and students' Self-Regulated Learning. This research is a quasi experimental research with the subject were VIII grade students of JHS 5 Surakarta in the academicyear 2022/2023 school year. The samples use two classes taken by cluster random sampling. Data collection technique were used documentation, tests, and questionnaires. The data analysis technique used a two-way variance analysis 2×3 unequal cells. The results of the analysis showed that: 1) Learning Cycle 7E learning model assisted by labyrinth board game and putar bawah game resulted is better mathematical reasoning ability than direct instruction; 2) Students with high self-regulated learning had better mathematical reasoning ability than low self-regulated learning; 3) There is no interaction between the learning model and students self-regulated learning.